2000
DOI: 10.1128/jvi.74.17.8111-8118.2000
|View full text |Cite
|
Sign up to set email alerts
|

The 5′ RNA Terminus of Spleen Necrosis Virus Stimulates Translation of Nonviral mRNA

Abstract: The RU5 region at the 5 RNA terminus of spleen necrosis virus (SNV) has been shown to facilitate expression of human immunodeficiency virus type 1 (HIV) unspliced RNA independently of the Rev-responsive element (RRE) and Rev. The SNV sequences act as a distinct posttranscriptional control element to stimulate gag RNA nuclear export and association with polyribosomes. Here we sought to determine whether RU5 functions to neutralize the cis-acting inhibitory sequences (INSs) in HIV RNA that confer RRE/Rev depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 46 publications
6
46
0
Order By: Relevance
“…10) (29). Expression from the EMCV IRES control was consistent with previous studies, being up-regulated 10-fold when compared with the no insert construct (24,49). Insertion of a synthetic hairpin sequence into a dicistronic vector was shown previously to inhibit expression of the 5Ј-ORF while simultaneously increasing expression of the 3Ј-ORF in the presence of an IRES (21).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…10) (29). Expression from the EMCV IRES control was consistent with previous studies, being up-regulated 10-fold when compared with the no insert construct (24,49). Insertion of a synthetic hairpin sequence into a dicistronic vector was shown previously to inhibit expression of the 5Ј-ORF while simultaneously increasing expression of the 3Ј-ORF in the presence of an IRES (21).…”
Section: Discussionsupporting
confidence: 74%
“…The insert was then subcloned into the modified pRL-CMV vector after digestion with XhoI and BamHI. The dicistronic construct containing the encephalomyocarditis virus insert was a kind gift from Dr. Kathleen Boris-Lawrie and was described previously (24). A hairpin structure was inserted into the dicistronic constructs by first generating an EcoRI site within the pRL-CMV promoter region upstream of the Renilla luciferase ORF.…”
mentioning
confidence: 99%
“…Recently, it was demonstrated that RHA is a necessary cofactor to promote translation initiation of highly structured mRNAs containing the post-transcriptional control element (PCE) Zhang and Grosse 2004;Hartman et al 2006). PCE is a highly structured, orientationdependent motif present in the 59 UTRs of some retroviral mRNAs (Butsch et al 1999;Roberts and Boris-Lawrie 2000;Hull and Boris-Lawrie 2002). The 59PCE activity is positively regulated by RHA and is essential for the translation efficiency of viral mRNAs (Butsch et al 1999;Hull and Boris-Lawrie 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both deletions affect the translational utilization of the respective RNAs (Fig. 3C), reminiscent of the role of the R/U5 region of spleen necrosis virus in translational regulation (44,45). The main finding of the current study is a novel function for the sequences downstream of the RSL, and especially for the PBS, in retroviral splice regulation.…”
Section: Discussionmentioning
confidence: 61%